2020
DOI: 10.1101/2020.12.03.20243626
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A holistic approach for suppression of COVID-19 spread in workplaces and universities

Abstract: As society has moved past the initial phase of the COVID-19 crisis that relied on broad-spectrum shutdowns as a stopgap method, industries and institutions have faced the daunting question of how to return to a stabilized state of activities and more fully reopen the economy. A core problem is how to return people to their workplaces and educational institutions in a manner that is safe, ethical, grounded in science, and takes into account the unique factors and needs of each organization and community. In thi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Testing programs are most helpful in certain working conditions 3 . For example, settings where employees work indoors without distancing for extended periods of time may particularly benefit from testing given the airborne nature of SARS-CoV-2 transmission 10 .…”
Section: Stratifying Employers By Workplace Typementioning
confidence: 99%
See 1 more Smart Citation
“…Testing programs are most helpful in certain working conditions 3 . For example, settings where employees work indoors without distancing for extended periods of time may particularly benefit from testing given the airborne nature of SARS-CoV-2 transmission 10 .…”
Section: Stratifying Employers By Workplace Typementioning
confidence: 99%
“…Modeling 3 and pilot studies 4,5 have shown that SARS-CoV-2 diagnostic testing programs are effective and feasible tools for limiting workplace transmission. Data on whether and how employers are testing their employees could provide important context for occupational health experts and public health officials as they formulate guidance that shapes employer precautions.…”
Section: Introductionmentioning
confidence: 99%
“…However, overly simplistic models can yield erroneous conclusions regarding real-world control strategies, so one must carefully balance model simplicity against the complex realistic elements most relevant to the problem at hand. Conventional compartmental COVID-19 control models are typically based on systems of ordinary differential equations (ODE's) (16,17,18,19,20,21,22,23,24,25). While ODE disease models provide a level of mathematical tractability, they necessitate the coupling of symptom status to specific model compartments, and this structural constraint can result in unnatural or unrealistic representations of symptom onset and presymtomatic transmission with potential unintended consequences on model behavior and real-world interpretations.…”
Section: Introductionmentioning
confidence: 99%
“…Although useful as simple baseline examples, these models may overestimate the efficacy of symptom-based COVID-19 controls due to the absence of presymptomatic transmission. A second more complicated class of ODE models includes a presymptomatic compartment where individuals are infectious but not yet symptomatic before transitioning to an infectious symptomatic compartment (22,23,24,25). This approach, while more realistic, presents challenges when interpreting results for real world decision making via comparisons to the simpler class of models.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, the COVID-19 pandemic presented a particular challenge for IHEs during the Fall 2020 semester [2][3][4][5][6][7]. On the one hand, bringing students back for on-campus and in-person education introduced the risk that an IHE would contribute to or exacerbate large regional outbreaks [8][9][10][11][12][13][14][15][16]; on the other hand, postponing students' return to campus may bring economic or social hardship to the communities in which the IHEs are embedded [17][18][19][20], since IHEs are often large sources of employment for counties across the United States. As a result, IHEs instituted a variety of "reopening" strategies during the Fall 2020 semester [21][22][23][24][25][26][27][28][29][30][31][32].…”
mentioning
confidence: 99%